Structure and bioactivities of a polysaccharide isolated from Ganoderma lucidum in submerged fermentation. Issue 5 (3rd September 2017) - Ai-lati, Aisikaer; Liu, Shuangping; Ji, Zhongwei; Zhang, Hao; Mao, Jian
ABSTRACT: In this study, a Ganoderma lucidum polysaccharide GLP-1–1 was isolated from a culture broth with Mw of 22014 Da. Monosaccharide contained glucose, mannose, and galactose with mole percentages of 92.33%, 7.55%, and 0.22%, respectively. Moreover, FTIR and methylation analysis were conducted to characterize the structural properties of GLP-1–1. The results of antioxidant activity analysis showed that GLP-1–1 had a great DPPH and ABTS radical scavenging activity. Meanwhile, GLP-1–1 also exhibited anti-tumor activity to A431 and MDA-MB-231 cells, and inhibitory rates were dose-dependent. During culturing with GLP-1–1, the G1/G0 cell percentage of A431 cells was increased from 48.64% to 84.52%, and the G1/G0 cell percentage of MDA-MB-231 cells was increased from 57.14% to 73.48%. Therefore, the anti-tumor activity of GLP-1–1 may be caused by inducing the G1/G0 arrest of tumor cells.